الأثر العباسي في الآراء النقدية لصاحب الفارياق - وفيق صابر, عمر (University of Eloued جامعة الوادي, 2013)
هدف هذا البحث إلى إظهار جذور النقد العباسي في الآراء النقدية لأحمد فارس الشدياق في مجموعة من كتبه خصوصاً (الفارياق)، نظراً لعمق تجربة الشدياق النقدية والأدبية وإطلالته الواسعة على الآداب العربية والغربية قديمها وحديثها مع التركيز على آرائه في الإبداع الشعري والتجربة والموهبة والإلهام، وكذلك أثر البيئة في ولادة المبدع مع تركيزه على لحظات الإبداع ومراحله وربطه الواضح بين الشعر والشعور وما يؤديه من تجربة شعرية فريدة. This study tends to show the roots of the Abbasi criticisim in the critical view of Ahmed Faris Al-Shodiaq in a group of his books especially the (Fariaq) because of Al-Shodiaq deep critical and literacy experience, in addition to his wide knowledge in Arabic and western literature (old and new). And a concentration on his creative views on poetic creativity , experience, talent and inspiration, besides the influence of the environment in the creation of a talented person with focus on the moments of creativity and its stages and his clear connection between poetry and feeling and how it leads to unique poetic experience. This research clarifies that Al-Shodiaq considers the values in poetry as relative and not absolute, refusing the traditional imitation which is different from simulation. Al-Shodiaq in his views about creativity tends to consider it as a talent rather than a ‘craft’. Accordingly he entered in many literary disputes with his contemporaries. This shows clearly the influence of old critics in Al-Shodiaq literary works such as: Bisher Ibn Al-Mutamer, Al-Jahedh, Abi-Dawood, Ibn- Tababa, Ibn-qutaibah, Al-Jurjani, Hasem Al-Kurtaji, Ibn-Sinan, Al-khafaji and many others. These critical roots clearly clarifies the extent of harmony between Al- Shodiaq and what appears in the views of modern critics such as Karomi and Ibn-Jawsan. This study concludes that Al-Shodiaq has mixed in his critical views between traditional and contemporary views. As he depends effectively on the Abbasi inherited critical views with a wide, clear and comprehensive look at modern literature and criticisim. A point that this study tends to explain.
مقال بمجلة البحوث والدراسات
Keywords: الأثر العباسي - آراء نقدية - صاحب الفارياق